Nanostructured Co3O4 grown on nickel foam: An efficient and readily recyclable 3D catalyst for heterogeneous peroxymonosulfate activation. (May 2018) - Yuan, Ruixia; Hu, Lin; Yu, Peng; Wang, Huaiyuan; Wang, Zhaohui; Fang, Jingyun
Abstract: Cobalt-based heterogeneous catalyst has been recognized as one of most efficient activators for peroxymonosulfate (PMS) decomposition, but usually suffers from the poor stability and difficulty to recover and reuse. Here easily recyclable cobalt oxide (Co3 O4 ) nanowires and nanoflowers grown on nickel foam (NF) are fabricated by a hydrothermal and calcination method. The prepared 3D Co3 O4 /NF catalyst is characterized and applied as a heterogeneous catalyst for PMS activation to generate sulfate radicals for decomposition of Acid Orange 7 (AO7). The results show that the AO7 degradation rate increases with cobalt loading and PMS dosage, but decreases with the increase of solution pH. The Co3 O4 /NF catalyst using 2 mM Co(NO3 )2 ·6H2 O as cobalt source exhibits highest activity, and almost complete decolorization could be achieved within 30 min. The diverse effects of coexisting anions (SO4 2−, HCO3 −, NO3 − and Cl − ) on AO7 degradation are observed and explained. After 10 consecutive runs, excellent catalytic reactivity of the catalyst remains while the level of leached cobalt during the catalyst usage is much lower than the maximum allowable concentration in drinking and natural water. More importantly, the macroscopic Co3 O4 /NF catalyst shows advantage of easy recycling after application compared to traditional catalysts. It is believed that the as-prepared Co3 O4 /NF is promising to be an effective and green heterogeneous catalyst for PMS activation to degrade organic pollutants for environmental application. Graphical abstract: Highlights: Novel Co3 O4 nanowires and nanoflowers are supported on nickel foam (NF) surface. Co3 O4 /NF exhibits excellent capacity for peroxymonosulfate activation. Macroscopic Co3 O4 /NF can be easily and completely recycled with low cobalt leaching. Co3 O4 /NF shows remarkable reusability with stable performance.